1995
DOI: 10.1177/001440299506200102
|View full text |Cite
|
Sign up to set email alerts
|

The Sociometric Status of Students with Disabilities in a Full-Inclusion School

Abstract: This study examined the sociometric status of children with disabilities in a full-inclusion school that did not use eligibility labels for special education services. The study used a positive and negative peer nomination technique to interview all students. The subject population included students with a range of disabilities; the majority were students with learning disabilities. Findings indicated significant differences between how students who were currently eligible for special education services and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 34 publications
5
63
1
8
Order By: Relevance
“…Students with special needs in inclusive settings are also typically rated lower on socio-metric scales than their peers. Students likely to be eligible for special education services but not yet "labeled" rated even lower than students already classified (Sale & Carey, 1995 (i.e. social inclusion).…”
Section: Social and Psychological Outcomesmentioning
confidence: 92%
See 1 more Smart Citation
“…Students with special needs in inclusive settings are also typically rated lower on socio-metric scales than their peers. Students likely to be eligible for special education services but not yet "labeled" rated even lower than students already classified (Sale & Carey, 1995 (i.e. social inclusion).…”
Section: Social and Psychological Outcomesmentioning
confidence: 92%
“…De Verdier (2016) found that many students with vision loss who were included in general education classes, in spite of the implementation of multiple interventions designed to enhance their social inclusion, were more likely than their non-disabled peers to experience loneliness and report other psychosocial problems. Other research suggests that students with disabilities experience greater social isolation in inclusive settings (Fraught, Balleweg, Crow, & Van den Pol, 1983;Peterson, 1982;Sale & Carey, 1995). Students with special needs in inclusive settings are also typically rated lower on socio-metric scales than their peers.…”
Section: Social and Psychological Outcomesmentioning
confidence: 99%
“…Katılımcıların dışlandıklarının farkında oldukları ve bundan dolayı çok üzüntü duydukları izlenimi edinilmiştir. Sosyometrik teknikler kullanılarak yürütülen araştırmalarda da bu bulguyu destekler bulgulara ulaşılmıştır (Akçamete ve Ceber, 1999;Baydık ve Bakkaloğlu, 2009;Friend, 2006;Sale ve Carey, 1995;Vuran, 2005). Özel gereksinimli öğrencilerin sosyal, duygusal ve davranışsal özellikleri göz önünde bulundurulduğunda, genellikle arkadaşlarıyla sorunlar yaşamaları beklenmekte (Huang ve Cuvo, 1997); bu araştırmanın bulguları ise durumun bu beklenenin aksine iyi olduğunu göstermektedir.…”
Section: "Okulda Arkadaşlarınla Ilişkilerin Nasıl?"unclassified
“…A study by Fryxell and Kennedy (1995) revealed that students with severe disabilities that were serviced in the general classroom made more social contacts and developed deeper friendships than students serviced in self-contained classrooms. However, students with disabilities in an inclusive classroom were still not picked as most liked and generally picked as least liked in student nominations (Sale & Carey, 1995). Bear et al (2002) concluded that students with learning disabilities attending an inclusive classroom did not seem harmed even though they were comparing themselves to their peers in the regular classroom.…”
Section: Self-concept and Placementmentioning
confidence: 99%